2bRAD reveals fine-scale genetic structuring among populations within the Mediterranean zoanthid Parazoanthus axinellae (Schmidt, 1862) - Marko Terzin; Adriana Villamor; Lorenzo Marincich; Kenan Matterson; Maria Grazia Paletta; Valentina Bertuccio; Giorgio Bavestrello; Lisandro Benedetti Cecchi; Elisa Boscari; Carlo Cerrano; Giovanni Chimienti; Leonardo Congiu; et al. (Coral Reefs, 2024)
The zoanthid Parazoanthus axinellae (Schmidt, 1862) is a widespread coral species in the Mediterranean coralligenous assemblages where two morphotypes are found: Slender and Stocky, differing in size, color, and preferred substrate. Due to these marked differences, Slender and Stocky morphotypes were hypothesized to be two species. Here, we used 2bRAD to obtain genome‐wide genotyped single nucleotide polymorphisms (SNPs) to investigate the genetic differentiation between Slender and Stocky morphs, as well as their population structure. A total of 101 specimens of P. axinellae were sampled and genotyped from eight locations along the Italian coastline. In four locations, samples of the two morphotypes were collected in sympatry. 2bRAD genome-wide SNPs were used to assess the genetic divergence between the two morphotypes (1319 SNPs), and population connectivity patterns within Slender (1926 SNPs) and Stocky (1871 SNPs) morphotypes. Marked and consistent differentiation was detected between Slender and Stocky morphotypes. The widely distributed Slender morphotype showed higher population mixing patterns, while populations of the Stocky morphotype exhibited a stronger genetic structure at a regional scale. The strong genetic differentiation observed between P. axinellae Slender and Stocky morphotypes provides additional evidence that these morphs could be attributed to different species, although further morphological and ecological studies are required to validate this hypothesis. Our study highlights the importance of resolving phylogenetic and taxonomic disparities within taxonomically problematic groups, such as the P. axinellae species complex, when performing genetic connectivity studies for management and conservation purposes. Graphical Abstract Schematic overview of the main genetic structuring patterns observed in this study. Coral polyps were colored to intuitively associate the reader to Parazoanthus axinellae morphotypes, with orange tones being attributed to the Stocky morphotype, and yellow tones to the Slender morphotype. Bidirectional arrows represent gene flow between coral individuals, with the number and thickness of arrows corresponding to the intensity of gene flow rates. The red dashed line represents the potential reproductive isolation between Slender and Stocky morphs

Sediment and bottom water eDNA metabarcoding to support coastal management - Alice Tagliabue; Kenan Oguz Matterson; Massimo Ponti; Eva Turicchia; Marco Abbiati; Federica Costantini (Ocean & Coastal Management, 2023)

Integrative taxonomy approach to detect spatial and temporal variability of the Mediterranean benthic communities through artificial substrate units (ASUs) - Francesco Mugnai; Barbara Mikac; Marina Antonia Colangelo; Kenan Oguz Matterson; Marco Abbiati; Federica Costantini (Frontiers in Marine Science, 2023)
Monitoring spatial and temporal changes of marine benthic communities using standardized procedures is essential to take necessary steps towards conservation of marine ecosystems. In this study we combined Artificial Substrate Units (ASUs) for sampling of benthic communities, with integrative taxonomy approach that incorporated morphological identification of organisms and COI DNA metabarcoding, to characterize the diversity of communities at three locations across the Central Mediterranean Sea (Livorno and Palinuro, Italy; Rovinj, Croatia) in 2019 and 2020. Significant differences in the communities’ structure were observed both at large spatial scale between sampled locations, and at small spatial scale (less than ten kilometers) between sites. Moreover, significant temporal variability in species richness and structure of benthic assemblages was detected, with higher richness in 2020. Revealed variability can probably be attributed to the peculiar geomorphological, oceanographical, and ecological features of locations, but also to the influence of interplaying local chemical and physical factors and biological processes such as species settlement, competition, and migration that can act at small spatial and temporal scales. The similarity in the species composition and community structure accessed by morphological and metabarcoding approaches was low, with only 16% of the species (out of 133 species identified overall) commonly detected by both approaches. This is mostly both due to a lack of data on COI sequences of numerous benthic invertebrates in the public barcoding databases on the one hand, and difficulties in detecting small and cryptic taxa through morphological analyses on the other. This suggests that combining of two approaches is required to fully describe the biodiversity of benthic assemblages. Finally, comparison of the spatial variability of the benthic communities’ structure with two approaches at different taxonomic levels, indicated that genus and family levels give results that are consistent to those obtained by the species level. This suggests that family level might be satisfactory in monitoring the spatial-temporal variability of Mediterranean hard bottom benthic communities.

Correction to: Population genomic structure of the black coral Antipathella subpinnata in Mediterranean Vulnerable Marine Ecosystems - Marko Terzin; Maria Grazia Paletta; Kenan Matterson; Martina Coppari; Giorgio Bavestrello; Marco Abbiati; Marzia Bo; Federica Costantini (Coral Reefs, 2021)

Population genomic structure of the black coral Antipathella subpinnata in Mediterranean Vulnerable Marine Ecosystems - Marko Terzin; Maria Grazia Paletta; Kenan Matterson; Martina Coppari; Giorgio Bavestrello; Marco Abbiati; Marzia Bo; Federica Costantini (Coral Reefs, 2021)
Antipathella subpinnata (Ellis and Solander 1786) is one of the most frequently observed black corals at mesophotic depths (60–200 m) of the Mediterranean Sea, particularly in the northwestern part of the basin, where its populations can reach high densities and create forest-like aggregations, both along the coast and in offshore locations such as seamounts. Similar to other marine underwater forests, black coral gardens host a rich associated fauna and attract numerous species of commercial interest. As such, these corals are targeted by recreational and artisanal fisheries and are vulnerable to human impact due to their arborescent morphology and low growth rates. Genetic connectivity can provide valuable insight into the processes of population maintenance and replenishment following environmental disturbance and is often used as a proxy for population resilience. In our study, a restriction-site associated DNA analysis (2bRAD) was used to evaluate fine-scale population structure of the Mediterranean black coral A. subpinnata , and to understand which populations could serve as a potential source of genetic diversity for adjacent populations. Colonies from two offshore localities (a Ligurian seamount and a Tyrrhenian canyon) and four coastal populations from Liguria and Sicily were sampled and genotyped. Significant genetic differentiation was recorded between coastal and offshore localities. Moreover, offshore localities were genetically distinct from one another, while all coastal populations were characterized by panmixia. This indicates that offshore A. subpinnata gardens are potentially less resilient to human impact (i.e., demersal fishing activities) due to a limited influx of larvae from adjacent habitats. In addition, they are unlikely to supply coral propagules to coastal populations. Overall, this study highlights the vulnerability of Mediterranean A. subpinnata forests, and the importance of enforcing conservation and management measures to achieve Good Environmental Status (GES, EU Marine Strategy Framework Directive) of these valuable marine ecosystems.

Abiotic conditions drive significant variability in nutrient processing by a common Caribbean sponge, Ircinia felix - Stephanie K. Archer; Julia L. Stevens; Ryann E. Rossi; Kenan O. Matterson; Craig A. Layman (Limnology and Oceanography, 2017)
Coral reefs typically occur in oligotrophic waters, where tight recycling of energy and nutrients is essential in order to support their high productivity. Sponges are efficient filter feeders that host diverse and abundant microbial communities that often contain members capable of carrying out complex nutrient transformations. Consequently, sponges often act as significant sources of bioavailable forms of nitrogen and phosphorus while acting as sinks for dissolved organic carbon (DOC). However, little attention has focused on variability of nutrient release by sponges and no studies have reported how abiotic conditions may impact sponge‐driven changes in nutrient concentrations. Here, we show that a common Caribbean sponge, Ircinia felix , is capable of being both a source and a sink for DOC, ammonium, nitrate/nitrite ( ), and phosphate ( ). Additionally, we show that abiotic conditions, particularly ambient nutrient availability, seem to explain a significant amount of the variability ( R 2 range from 0.40 to 0.65). Interestingly, as ambient nutrient concentrations increased, I. felix transitioned from acting as a source to serving as a sink for all nutrient forms measured. We also found I. felix ‐associated bacteria exhibit a significantly higher abundance of predicted nitrogen metabolism, carbon fixation, and photosynthetic genes relative to ambient water and sediment. These results suggest that sponges play an important and dynamic role in biogeochemical cycling on reefs, particularly as human activities alter natural nutrient dynamics in coastal systems.